PENGARUH VARIASI PRODUK, STORE ATMOSPHERE, DAN SERVICE QUALITY TERHADAP MINAT BELI ULANG PADA CASSAVA COFFEE - Made Mitha Aprilia Pratiwi; Ni Putu Cempaka Dharmadewi Atmaja (Jurnal Bakti Saraswati (JBS), 2024)
This research aims to determine the influence of product variants, store atmosphere and service quality on repurchase interest in Cassava Coffee. The research was conducted at Cassava Coffee which is located in Br. Sedahan, Gulingan, Mengwi District, Badung Regency. The research objects in this study are product variety, store atmosphere, and service quality on repurchase interest in Cassava Coffee. In this research there are 16 indicators, so the number of samples used is, sample = 5 X 16 number of indicators = 80 respondents with data collection methods namely observation, interviews, documentation and questionnaires. The analysis technique used is multiple linear regression analysis using the SPSS version 26 program. Based on the results of the analysis, this research shows that product variations have a positive and significant effect on repurchase interest in Cassava Coffee in Badung Regency. This means that the greater the variety of products provided by Cassava Coffee in Badung Regency, the more it will be able to attract repeat purchase interest. Store atmosphere has a positive and significant effect on repurchase interest in Cassava Coffee in Badung Regency. This means that the better the consumer store atmosphere towards Cassava Coffee in Badung Regency, the more interest they will buy. Service quality has a positive and significant effect on repurchase interest in Cassava Coffee in Badung Regency. Cassava Coffee in Badung Regency by providing the best quality service to consumers will increase interest in repeat purchases.